A theory of discrimination law - Khaitan, Tarunabh, 1981- (Oxford : Oxford University Press, 2015)
This volume provides a general theory of discrimination law as practised in liberal democratic jurisdictions. Rejecting accounts that place the value of equality at the heart of the law, it argues that discrimination law protects individual autonomy. Applying the theory, the book tackles the central legal problems in applying discrimination laws.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 16, 2015).
Keywords: Discrimination -- Law and legislation -- Philosophy; Discrimination -- Law and legislation